Legal Protection of Occupational Health and Safety for Cleaning Service Workers at RSUD Salatiga: Perlndungan Hukum Kesehatan dan Keselamatan Kerja Terhadap Cleaning Service di RSUD Salatiga - Pramesti, Nadila Putri; Yuspin, Wardah (Prosiding University Research Colloquium, 2024)
Legal protection in the context of occupational health and safety (OHS) is crucial for ensuring the safety and well-being of workers in the workplace. In Indonesia, legal regulations govern the aspects of OHS in the employment relationship between workers/labourers and employers. This research aims to analyze the legal protection of OHS in Indonesia, its implementation on cleaning service workers at the Regional General Hospital (RSUD) Salatiga.. This study employs an empirical juridical approach, collecting data through interviews, observations, and documentation. Data analysis is conducted qualitatively by merging legal analysis with empirical data. The results of this study showing the legal protection of OHS in Indonesia is based on the 1945 Constitution and legal regulations, including Law Number 1 of 1970 on Occupational Safety and Health. Hospitals must adhere to OHS laws, cleaning service workers need to be more aware of reporting accidents, bipartite negotiations should be considered for dispute resolution, and contracts with service providers must ensure adequate OHS protection.